Activity of N-Phenylpiperazine Derivatives Against Bacterial and Fungal Pathogens - Pospisilova, Sarka; Marvanova, Pavlina; Treml, Jakub; Moricz, Agnes M; Ott, Peter G; Mokry, Petr; Odehnalova, Klara; Sedo, Ondrej; Cizek, Alois; Jampilek, Josef (Current protein & peptide science, 2019)
BACKGROUND: As the bacterial resistance to antibacterial chemotherapeutics is one of the greatest problems in modern medicine, efforts are made to develop new antimicrobial drugs. Compounds with a piperazine ring have proved to be promising agents against various pathogens. OBJECTIVE: The aim of the study was to prepare a series of new N-phenylpiperazines and determine their activity against various pathogens. METHOD: Target compounds were prepared by multi-step synthesis starting from an appropriate substituted acid to an oxirane intermediate reacting with 1-(4-nitrophenyl)piperazine. Lipophilicity and pKa values were experimentally determined. Other molecular parameters were calculated. The inhibitory activity of the target compounds against Staphylococcus aureus, four mycobacteria strains, Bipolaris sorokiniana, and Fusarium avenaceum was tested. In vitro antiproliferative activity was determined on a THP-1 cell line, and toxicity against plant was determined using Nicotiana tabacum. RESULTS: In general, most compounds demonstrated only moderate effects. 1-(2-Hydroxy-3-{[4-(propan- 2-yloxy)benzoyl]oxy}propyl)-4-(4-nitrophenyl)piperazinediium dichloride and 1-{3-[(4-butoxybenzoyl)- oxy]-2-hydroxypropyl}-4-(4-nitrophenyl)piperazinediium dichloride showed the highest inhibition activity against M. kansasii (MIC = 15.4 and 15.0 µM, respectively) and the latter also against M. marinum (MIC = 15.0 µM). 1-(2-Hydroxy-3-{[4-(2-propoxyethoxy)benzoyl]oxy}propyl)-4-(4-nitrophenyl)piperazinediium dichloride had the highest activity against F. avenaceum (MIC = 14.2 µM). All the compounds showed only insignificant toxic effects on human and plant cells. CONCLUSION: Ten new 1-(4-nitrophenyl)piperazine derivatives were prepared and analyzed, and their antistaphylococcal, antimycobacterial, and antifungal activities were determined. The activity against M. kansasii was positively influenced by higher lipophilicity, the electron-donor properties of substituent R and a lower dissociation constant. The exact mechanism of action will be investigated in follow-up studies.
Keywords: Microbial Sensitivity Tests; synthesis.; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; antifungální látky; mikrobiální testy citlivosti; antimycobacterials; antibakteriální látky; antifungals; N-phenylpiperazines; Drug Design; Anti-Bacterial Agents; Antifungal Agents; piperaziny; racionální návrh léčiv; dissociation constant; Piperazines; cytotoxicity; lipophilicity